2020
DOI: 10.1186/s12883-020-01925-8
|View full text |Cite
|
Sign up to set email alerts
|

Unruptured aneurysmal clipping complicated by delayed and refractory vasospasm: case report

Abstract: Background Delayed symptomatic vasospasm is a rare complication following clipping of an unruptured intracranial saccular aneurysm. There have been ten reported cases of delayed symptomatic vasospasm and only two of these occurred after 2 weeks from initial intervention. Our case is the first to document the refractory nature of such vasospasm despite aggressive first line therapy. Case presentation Here, we present a 67-year-old female who had surgical clipping of a 10x7mm right middle cerebral artery (MCA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Cerebral vasospasm, which is relatively uncommon, has been reported to occur after the clipping of a UIA. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] Here, we reported a case of a middle-aged female who suffered from an ischemic stroke due to severe vasospasm following successful treatment of an unruptured MCA bifurcation aneurysm. The pathomechanism of the unexpected severe vasospasm remains unclear.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Cerebral vasospasm, which is relatively uncommon, has been reported to occur after the clipping of a UIA. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] Here, we reported a case of a middle-aged female who suffered from an ischemic stroke due to severe vasospasm following successful treatment of an unruptured MCA bifurcation aneurysm. The pathomechanism of the unexpected severe vasospasm remains unclear.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, ischemic events following unpredictable delayed vasospasm after clipping have been reported in UIA patients. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] Here, we report a case in which delayed vasospasm and ischemic stroke accompanied by intractable headache occurred 1 week after the successful clipping of an unruptured MCA bifurcation aneurysm.…”
Section: Introductionmentioning
confidence: 91%
“…Currently, there are several options for treating unruptured intracranial aneurysms, including surgical clipping and different endovascular procedures. Still, minimally invasive endovascular coiling is frequently used and is considered the treatment of choice ( 19 , 20 ). Combined endovascular treatment with stent-assisted coil embolization of the aneurysm was performed successfully in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…bPeterson et al 42 reported the results of 4 ICA, 4 MCA, and 1 PCA aneurysms in a literature review involving vasospasms that develop after clipping intracranial aneurysms. The results showed that aphasia and hemiparesis can develop from vasospasm in the ICA and MCA territories.…”
mentioning
confidence: 99%
“…ACA, anterior cerebral artery; ACoA, anterior choroidal arteries; ICA, internal cerebral artery; Lla, lateral lenticulostriate artery; MCA, middle cerebral artery; Mla, medial lenticulostriate artery; PCA, posterior cerebral artery.aElkordy et al 41 reported that among 13 patients who underwent ACoA endovascular embolization to treat AVM, 1 developed transient hemiparesis-dysarthria and 1 developed hemiparesis–hemianopsia, after 4 had developed ischemia. These clinical symptoms could have resulted from ACoA injury affecting the globus pallidus.bPeterson et al 42 reported the results of 4 ICA, 4 MCA, and 1 PCA aneurysms in a literature review involving vasospasms that develop after clipping intracranial aneurysms. The results showed that aphasia and hemiparesis can develop from vasospasm in the ICA and MCA territories.…”
mentioning
confidence: 99%